Temporary central diabetes insipidus due to pneumocephalus secondary to posterior fossa surgery - A review of tension Pneumocephalus - Kaplan, Metin; Ozturk, Mehmet B.; Erol, Fatih S.; Dogukan, Ayhan; Yakar, Huseyin (Lippincott Williams & Wilkins, 2007)
There is a controversy over the seated position in neurosurgery. Despite some of its advantages, it also brings along some serious complications as well. One of these complications is pneumocephalus. Central diabetes insipidus (DI) secondary to pneumocephalus has not yet been reported in the literature. We present here a case of temporary central DI that occurred after posterior fossa surgery. To establish the diagnosis, other central and nephrogenic causes of DI should be eliminated. Symptoms of DI secondary to pneumocephalus improve when pneumocephalus is alleviated.
Keywords: complication of posterior fossa surgery; pneumocephalus; diabetes insipidus